2018
DOI: 10.3389/fnhum.2018.00159
|View full text |Cite
|
Sign up to set email alerts
|

Long-Range Temporal Correlations in Alpha Oscillations Stabilize Perception of Ambiguous Visual Stimuli

Abstract: Ongoing brain dynamics have been proposed as a type of “neuronal noise” that can trigger perceptual switches when viewing an ambiguous, bistable stimulus. However, no prior study has directly quantified how such neuronal noise relates to the rate of percept reversals. Specifically, it has remained unknown whether individual differences in complexity of resting-state oscillations—as reflected in long-range temporal correlations (LRTC)—are associated with perceptual stability. We hypothesized that participants w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…DFA was chosen since it requires less strict assumptions about the stationarity of the signal than the classical auto-correlation function or power spectral density (Linkenkaer-Hansen et al, 2001;Hardstone et al, 2012;Sangiuliano Intra et al, 2018), and its power-law exponent estimates are robust even when removing large portions of the data or when analyzing data that have been stitched together (Chen et al, 2002). Furthermore, the choice of DFA allowed direct comparisons with the existing literature on scale-free behavior in neuronal data.…”
Section: Methodsmentioning
confidence: 99%
“…DFA was chosen since it requires less strict assumptions about the stationarity of the signal than the classical auto-correlation function or power spectral density (Linkenkaer-Hansen et al, 2001;Hardstone et al, 2012;Sangiuliano Intra et al, 2018), and its power-law exponent estimates are robust even when removing large portions of the data or when analyzing data that have been stitched together (Chen et al, 2002). Furthermore, the choice of DFA allowed direct comparisons with the existing literature on scale-free behavior in neuronal data.…”
Section: Methodsmentioning
confidence: 99%
“…It has been suggested that the temporal correlations of amplitude modulation of oscillations on time scales of seconds to tens of seconds may be important for the temporal integrity of cognition, since a reduction of scaling exponent is related to several neurological impairments and diseases (Hausdorff et al, 2001 ; Parish et al, 2004 ; Linkenkaer-Hansen et al, 2005 ; Montez et al, 2009 ). Moreover, a more whitened state, characterized by a lower scaling exponent, has been found to lead more often to percept destabilization (Sangiuliano Intra et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been exhibited that various time series extracted from biological systems, including electrocardiography (ECG) [21,22], electroencephalography (EEG) [23][24][25][26][27][28][29][30][31][32][33][34][35], signal neuron discharge [36] and human gait [37] behave as scale-invariant processes. The power-law scaling studies have shown the of the behaviors in the complex biological systems [38][39][40][41][42]. The indicates that there are properties for a large portion of systems which are independent of the dynamics of systems.…”
Section: Introductionmentioning
confidence: 99%